Risk implications of the new CKD Epidemiology Collaboration (CKD-EPI) equation compared with the MDRD Study equation for estimated GFR: the Atherosclerosis Risk in Communities (ARIC) Study - Matsushita, Kunihiro; Selvin, Elizabeth; Bash, Lori D; Astor, Brad C; Coresh, Josef (American journal of kidney diseases, 2010)
The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) recently published an equation for estimated glomerular filtration rate (eGFR) using the same variables (serum creatinine level, age, sex, and race) as the Modification of Diet in Renal Disease (MDRD) Study equation. Although the CKD-EPI equation estimates GFR more precisely compared with the MDRD Study equation, whether this equation improves risk prediction is unknown. Prospective cohort study, the Atherosclerosis Risk in Communities (ARIC) Study. 13,905 middle-aged participants without a history of cardiovascular disease with median follow-up of 16.9 years. eGFR. We compared the association of eGFR in categories (>or=120, 90-119, 60-89, 30-59, and <30 mL/min/1.73 m(2)) using the CKD-EPI and MDRD Study equations with risk of incident end-stage renal disease, all-cause mortality, coronary heart disease, and stroke. The median value for eGFR(CKD-EPI) was higher than that for eGFR(MDRD) (97.6 vs 88.8 mL/min/1.73 m(2); P < 0.001). The CKD-EPI equation reclassified 44.9% (n = 3,079) and 43.5% (n = 151) of participants with eGFR(MDRD) of 60-89 and 30-59 mL/min/1.73 m(2), respectively, upward to a higher eGFR category, but reclassified no one with eGFR(MDRD) of 90-119 or <30 mL/min/1.73 m(2), decreasing the prevalence of CKD stages 3-5 from 2.7% to 1.6%. Participants with eGFR(MDRD) of 30-59 mL/min/1.73 m(2) who were reclassified upward had lower risk compared with those who were not reclassified (end-stage renal disease incidence rate ratio, 0.10 [95% CI, 0.03-0.33]; all-cause mortality, 0.30 [95% CI, 0.19-0.48]; coronary heart disease, 0.36 [95% CI, 0.21-0.61]; and stroke, 0.50 [95% CI, 0.24-1.02]). Similar results were observed for participants with eGFR(MDRD) of 60-89 mL/min/1.73 m(2). More frequent reclassification of younger, female, and white participants explained some of these trends. Net reclassification improvement in participants with eGFR < 120 mL/min/1.73 m(2) was positive for all outcomes (P < 0.001). Limited number of cases with eGFR < 60 mL/min/1.73 m(2) and no measurement of albuminuria. The CKD-EPI equation more appropriately categorized individuals with respect to long-term clinical risk compared with the MDRD Study equation, suggesting improved clinical usefulness in this middle-aged population.